solve by substituting 5x+y=5
If we subtract 5x from both sides of the first equation we get: y = -5x + 5
We can substitute this value of "y" into the second equation:
9x - 4(-5x + 5) = -20
Distribute: 9x + 20x - 20 = -20
29x - 20 = -20; add 20 to both sides
29x = 0; x = 0
Substitute 0 in for x in one of the equations and we get: y = -5(0) + 5
y = 5
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?